2021
DOI: 10.1177/0271678x211024373
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal collateral activation indicates severely impaired cerebrovascular reserve capacity in patients with symptomatic unilateral carotid artery occlusion

Abstract: For patients with symptomatic unilateral internal carotid artery (ICA) occlusion, impaired cerebrovascular reactivity (CVR) indicates increased stroke risk. Here, the role of collateral activation remains a matter of debate, whereas angio-anatomical collateral abundancy does not necessarily imply sufficient compensatory flow provided. We aimed to further elucidate the role of collateral activation in the presence of impaired CVR. From a prospective database, 62 patients with symptomatic unilateral ICA occlusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…When the ICA has severe stenosis, the primary collateral is the first initiated intracranial flow to supply the hypoperfused cerebral hemisphere, and the secondary collateral flow is initiated consequently when the primary collateral in the Willis circle is insufficient. [12][13][14][15] In the present study, when the right carotid artery had stenosis >70%, the right anterior, middle, and posterior cerebral arteries were first initiated to support the hypoperfused right cerebral hemisphere. Flow direction change of a certain specific artery implies insufficient supply via the primary collateral circulation of the Willis circle.…”
Section: Discussionmentioning
confidence: 67%
“…When the ICA has severe stenosis, the primary collateral is the first initiated intracranial flow to supply the hypoperfused cerebral hemisphere, and the secondary collateral flow is initiated consequently when the primary collateral in the Willis circle is insufficient. [12][13][14][15] In the present study, when the right carotid artery had stenosis >70%, the right anterior, middle, and posterior cerebral arteries were first initiated to support the hypoperfused right cerebral hemisphere. Flow direction change of a certain specific artery implies insufficient supply via the primary collateral circulation of the Willis circle.…”
Section: Discussionmentioning
confidence: 67%
“…Sebok and Sobczyk et al observed a significant correlation between CVR and collateral development. 9,10 The pattern of collateral blood flow resulting from carotid artery stenosis can be categorized into primary pathways, such as those through the circle of Willis from the contralateral ICA and VA, and secondary pathways, including routes via the external carotid artery, ophthalmic artery, and leptomeningeal vessels. 23 In our study, collateral flow evaluations were primarily focused on routes other than leptomeningeal anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has reported that the presence of collateral flow is a prerequisite for the impaired CVR caused by carotid artery stenosis. 9,10 In our earlier study on BeamSAT MRI, 6,7 we observed discrepancies in the time-of-flight (TOF) signal intensity of the MCA between conventional and ICA-selective MRA in certain cases. Additionally, contralateral ICA-selective MRA and VA-selective MRA showed cross flow or collateral flow to the MCA on the stenotic side in some cases.…”
Section: Introductionmentioning
confidence: 95%
“…Such information is needed to better understand the signaling proteins within the collaterogenesis pathway and aid studies investigating the genetic basis for differences in collaterals among humans. [73][74][75] It is also needed for translation going forward, given that collateral imaging is frequently performed in stroke patients, and that the levels of regional recruitment of collateral flow have been shown to predict stroke outcomes [1][2][3][4][5][6][7][8]76 or indicate carotid artery occlusion, 77 and that recent studies have shown that new collaterals form in brain and heart following acute arterial occlusion as well as after several weeks of systemic hypoxemia. 35,54,63 Identification of candidate "collateral genes" in mice will enable their testing for confirmation in humans using single-gene SNP association analysis, with its significant statistical advantage over GWAS, against collateral score (and/or other ordinal or continuous-variable surrogate endophenotypes) in brain, [1][2][3][4][5][6] and collateral flow index in heart and lower extremities, 10,11 in patients with vascular obstruction, chronic hypoxemia and hemoglobinopathies, and in healthy individuals adapted to reduced oxygen availability (with the caveat that collateral flow in the setting of obstruction is dependent on more than collateral number and diameter).…”
Section: Discussionmentioning
confidence: 99%